1996
DOI: 10.1177/002193479602600609
|View full text |Cite
|
Sign up to set email alerts
|

What Next?

Abstract: It has been argued that during the 200 years since the French Revolution, its ideals of liberty, equality, and fraternity gradually have become more visible in societies throughout the world. In other words, societies, in one form or another, have tended to walk the path toward the realization of universal ideals; the decline of racial and ethnic prejudice, the acceptance of cultures other than one's own, and the role of the various means of communication in providing fast information about peoples that were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Although Jim Crow eliminated any legally recognized complexion differences (Davis 1991;Penha-Lopes 1996), social and economic differences persisted within the African American community. Sociological studies beginning in the 1960s found that modern mixedrace people earned higher incomes, accumulated more wealth, received better educations, worked at better jobs, and even improved their marriage chances.…”
Section: The Economic and Social Consequences Of Complexionmentioning
confidence: 99%
“…Although Jim Crow eliminated any legally recognized complexion differences (Davis 1991;Penha-Lopes 1996), social and economic differences persisted within the African American community. Sociological studies beginning in the 1960s found that modern mixedrace people earned higher incomes, accumulated more wealth, received better educations, worked at better jobs, and even improved their marriage chances.…”
Section: The Economic and Social Consequences Of Complexionmentioning
confidence: 99%